Formative dimensions of news practices of adults counselling: two case studies - Salini, Deli (Swiss Journal of Educational Research, 2017)
The purpose of this contribution is to highlight the formative implications of adult counselling from the cross-sectional analysis of two case studies on recent practices in the field. This analysis will highlight some elements of counselling situations that contribute to the emergence of new knowledge in the concerned individuals. These elements are: i) facilitated access to a selection of information and its appropriate use; ii) support in the development of their inquiry process, in relation to a professional development or training project. This is made possible through the implementation by counsellors of a set of modalities for the transmission of new knowledge, in which the mimetic, dialogical and fictional dimensions are particularly present.